Do the flipped impacts of hotels matter to the popularity of Airbnb?. Issue 6 (4th February 2021) - Yi, Bowen; Shi, Da; Shi, Fangfang; Zhang, Liang
Abstract : Purpose: By building on cooperation–competition theory, this study aims to investigate the multidimensional flipped effects of neighborhood hotels on Airbnb listings' popularity, examining the degree to which such impacts are influenced by hotel types and geographical areas. Design/methodology/approach: This study explores the interdependent and competitive relationship between neighborhood hotels and Airbnb from the perspective of effects on Airbnb listings' popularity by exploring a data set covering 10, 492 Airbnb listings and 2, 691 hotels from Ctrip. Findings: Results reveal that neighborhood hotels' number of reviews, review ratings and prices each have positive spillover effects on Airbnb listings' popularity, while quality assurance labels and negative review topic sentiments exert competitive effects on Airbnb popularity. Moreover, the number of budget chain hotels and high-star hotels have positive and negative effects on Airbnb popularity, respectively. Geographical areas also have a moderating effect on the relationship between various hotel-related influencing factors and Airbnb. Practical implications: This study can offer hotel managers and Airbnb operators a clearer understanding of these businesses' coexisting relationship. Findings can also provide Airbnb-specific guidelines for practitioners in terms of site selection, promotional features and development strategies for Airbnb listings. Originality/value: This study establishes a cooperation–competition relationship model between hotels and Airbnb and considers the flipped effects of hotels on Airbnb for the first time. It expands previous studies by considering the multidimensional effects of hotels on Airbnb listings' popularity and by examining the influences of hotel types and geographical areas on hotels' impacts on Airbnb.